L’émoi des mots. Propos liminaires sur le féodal* - Blaise Dufal (L'Atelier du CRH)
For more than a century, the feudal* was at the center of medieval science and at the heart of the interpretation of medieval societies. This centrality has been accompanied by multiple contrasting emotions expressed by historians about these notions and terms, more or less vague, more or less well defined. These very surprising emotions appear regularly in the writings of medievalists, and analyzed from a historiographical point of view, encourage us to tell another story of feudal*, that of the echoes that these words resound. It is not a question of deciding in the specialists’ controversies, it is then a question of trying to apprehend in a renewed way some of these multiple and complex scientific debates (feudal transformation, nominalist criticism, Marxist feudalism) to understand its academic and ideological issues. The feudal* poses important epistemological questions, particularly regarding to the relationship of historians with words, with their own discourses and their alleged theories. The quasi-disappearance of feudal* observed in recent decades is endless, and we must wonder both about the reasons for this abandonment and the meaning of what is resisting in it.